The Influence of Natural Resources, Energy Consumption, and Renewable Energy on Economic Growth in ASEAN Region Countries - Rusiadi, Rusiadi; Hidayat, Muhammad; Rangkuty, Dewi Mahrani; Ferine, Kiki Farida; Saputra, Jumadil (International Journal of Energy Economics and Policy, 2024)
This research aims to identify and analyze the role of natural resources, CO2 emissions, and renewable energy on the economic growth of countries in the ASEAN region. In this study, we tested whether a dynamic process occurred based on a dynamic panel data model while comparing it with static panel data. The dataset used is ASEAN region countries with time series data from 2000-2021. The analysis tools used are static and dynamic panel data. The research results found that natural resources, FDI, and renewable energy significantly positively affect economic growth in the ASEAN region. Conversely, CO2 has a negative and insignificant effect. These results prove that the ASEAN region’s economic development has been clean energy-oriented.